Chromatin: the old and young of it - Emerson, Felicity J.; Lee, Siu Sylvia (Frontiers in Molecular Biosciences, 2023)
Aging affects nearly all aspects of our cells, from our DNA to our proteins to how our cells handle stress and communicate with each other. Age-related chromatin changes are of particular interest because chromatin can dynamically respond to the cellular and organismal environment, and many modifications at chromatin are reversible. Changes at chromatin occur during aging, and evidence from model organisms suggests that chromatin factors could play a role in modulating the aging process itself, as altering proteins that work at chromatin often affect the lifespan of yeast, worms, flies, and mice. The field of chromatin and aging is rapidly expanding, and high-resolution genomics tools make it possible to survey the chromatin environment or track chromatin factors implicated in longevity with precision that was not previously possible. In this review, we discuss the state of chromatin and aging research. We include examples from yeast, Drosophila, mice, and humans, but we particularly focus on the commonly used aging model, the worm C. elegans, in which there are many examples of chromatin factors that modulate longevity. We include evidence of both age-related changes to chromatin and evidence of specific chromatin factors linked to longevity in core histones, nuclear architecture, chromatin remodeling, and histone modifications.